Thrombotic Complications after COVID-19 Vaccination: Diagnosis and Treatment Options - Katharina Guetl; Reinhard Bernd Raggam; Thomas Gary (Biomedicines, 2022)
Coronavirus disease 2019 (COVID-19) vaccines were developed a few months after the emergence of the pandemic. The first cases of vaccine-induced thrombotic complications after the use of adenoviral vector vaccines ChAdOx1 nCoV-19 by AstraZeneca, and Ad26.COV2.S by Johnson & Johnson/Janssen, were announced shortly after the initiation of a global vaccination program. In these cases, the occurrence of thrombotic events at unusual sites—predominantly located in the venous vascular system—in association with concomitant thrombocytopenia were observed. Since this new entity termed vaccine-induced thrombotic thrombocytopenia (VITT) shows similar pathophysiologic mechanisms as heparin-induced thrombocytopenia (HIT), including the presence of antibodies against heparin/platelet factor 4 (PF4), standard routine treatment for thrombotic events—arterial or venous—are not appropriate and may also cause severe harm in affected patients. Thrombotic complications were also rarely documented after vaccination with mRNA vaccines, but a typical VITT phenomenon has, to date, not been established for these vaccines. The aim of this review is to give a concise and feasible overview of diagnostic and therapeutic strategies in COVID-19 vaccine-induced thrombotic complications.